Dynamique des relations santé–environnement - Clémence Massart (Revue d'anthropologie des connaissances)
This article questions the ecological trend (“écologisation”) at work in the qualification of Lyme disease. Overall, “écologisation” means the process by which the society takes into account the environmental aspects in its development. The institutional aspects of the “écologisation” have been widely investigated. In this article, I will focus primarily another form of “écologisation”, those practices which involves a diversification of actors, issues, questions and judged legitimate knowledge. I will examine these two forms of “écologisation” through two spaces in which to meet particular ecologists, physicians and patients around an attempted integrated definition of Lyme disease. Analysis of these areas show that alongside institutional, epistemic factors also demonstrate their importance as to the possibilities of dialogue between actors.